Fluxos de capital no Brasil no período de 2000-2014 : investigação sobre fatores pull e push - Pederiva, Ana Carolina (2015)
The present study analyzes the dynamics of entries and exits of foreign investment in Brazil and the importance of de domestic determinants (pull) and external determinants (push) in the attraction of these investments . The methodology adopted was the model of regressive factors (VAR), with monthly data from January 2000 to December 2014 for total investment, direct investment, portfolio and others investments. The results demonstrate the importance of American production index as an external determinant factor of capital flows and the interest rate as a domestic determinant factor. The results also indicate the different kinds of flow that present different responses to the variables studied. We highlighted for example, the predominance of internal factors in determining the inflow and outflow of direct investment. In general, the results allow to conclude that as internal factors as external factors to the Brazilian were relevant in the attractions of capital in that period.